The joy of smoking and salt curing : the complete guide to smoking and curing meat, fish, game, and more - Burch, Monte. frey50 (New York : Skyhorse Pub., 2011)
Introduces beginners to the ancient art of preserving meat, fish, and game with full-color photographs and clear instructions on how to select meats and avoid contamination, how to choose smokers, and how to use various tools. Also includes recipes for rubs, sauces, and marinades.
Includes index.
Keywords: Smoked foods; Salting of food